2021
DOI: 10.53730/ijhs.v5n3.1773
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare facilities management in digitalization context

Abstract: In 2020-2021, the digitalization of medical institutions and their management systems is one of them during the coronavirus pandemic. This research reveals that the healthcare system crisis due to the spread of the pandemic not only revealed weaknesses but was an engine for accelerating technological change even in the face of limited financial resources. In Germany, Italy and France the crisis provided: 1) the development of telemedicine and online tools (to assist departments of medical institutions and doct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…For example, at the first diagnosis, an individual with a family history of Diabetes mellitus identifies a slight lowering of EGFR below the normal level, later they come up with a higher risk of kidney disease. The progress of worsening kidney function among construction workers who have been ingesting energy drinks for years might have resulted from a complex process related to individual and environmental factors (Nataliia et al, 2021). Current findings add to the body of knowledge whereas the following factors, first, family history of comorbidity adds a risk factor in altering kidney function among those with extended ingestion of energy drinks.…”
Section: Discussionmentioning
confidence: 66%
“…For example, at the first diagnosis, an individual with a family history of Diabetes mellitus identifies a slight lowering of EGFR below the normal level, later they come up with a higher risk of kidney disease. The progress of worsening kidney function among construction workers who have been ingesting energy drinks for years might have resulted from a complex process related to individual and environmental factors (Nataliia et al, 2021). Current findings add to the body of knowledge whereas the following factors, first, family history of comorbidity adds a risk factor in altering kidney function among those with extended ingestion of energy drinks.…”
Section: Discussionmentioning
confidence: 66%
“…This study aims to gain a deeper understanding of the effect of telemedicine on patient satisfaction. This study explores telemedicine and patient satisfaction from the point of view of doctors, patients using telemedicine, and prospective patients using telemedicine on patient satisfaction in health care facilities (Nataliia et al, 2021).…”
Section: Interview Resultsmentioning
confidence: 99%
“…Zimmermanova et al (2022) state that the different levels of management in the medical units consider digitalisation as an essential information resource. Moreover, Nataliia et al (2021) grounded these findings because their results suggested that in the COVID-19 pandemic context, the digitalisation of the healthcare system of medical institutions and their management benefited from various facilities. Therefore, the results indicated that based on the pandemic crisis in the health system caused by the spread of the COVID-19 virus, technological change has accelerated, bringing benefits related to the exchange and storage of information by medical unit management through the implementation of various digital technologies in the healthcare system.…”
Section: Literature Reviewmentioning
confidence: 89%